A cost analysis of treatment of tibial fracture nonunion by bone grafting or bone morphogenetic protein-7. - Dahabreh, Z; Calori, G M; Kanakaris, N K; Nikolaou, V S; Giannoudis, P V (Int Orthop, 2009)
The parameter of health economics in the use of any contemporary medical module plays a dominant role in decision making. A prospective nonrandomised comparative study of the direct medical costs on the first attempt of treating aseptic nonunions of tibial fractures, with either autologous-iliac-crest-bone-graft (ICBG) or bone morphogenetic protein-7 (BMP-7), is presented. Twenty-seven consecutive patients, who were successfully treated for fracture nonunions, were divided into two groups. Group 1 (n = 12) received ICBG and group 2 (n = 15) received BMP-7. All patients healed their nonunions, and the financial analysis presented represents a best-case scenario. Three out of 12 of the ICBG group required revision surgery while just one out of 15 required it in the BMP-7 group. Average hospital stay was 10.66 vs. 8.66 days, time-to-union 6.9 vs. 5.5 months, hospitals costs pound2,133.6 vs. pound1,733.33, and theatre costs were pound2,413.3 vs. pound906.67 for the ICBG and BMP-7 groups, respectively. The BMP-7 cost was pound3002.2. Fixation-implant was pound696.4 vs. pound592.3, radiology pound570 vs. pound270, outpatient pound495.8 vs. pound223.33, and other costs were pound451.6 vs. pound566.27 for the ICBG and BMP-7 groups, respectively. The average cost of treatment with BMP-7 was 6.78% higher (P = 0.1) than with ICBG, and most of this (41.1%) was related to the actual price of the BMP-7. In addition to the satisfactory efficacy and safety of BMP-7 in comparison to the gold standard of ICBG, as documented in multiple studies, its cost effectiveness is advocated favourably in this analysis.
Keywords: Bone Morphogenetic Protein 7; Bone Transplantation; Cost-Benefit Analysis; Female; Fracture Fixation, Internal; Fractures, Ununited; Health Care Costs; Humans; Ilium; Male; Prospective Studies; Recombinant Proteins; Recovery of Function; Tibial Fractures; Treatment Outcome